Мент: [роман] / Сергей Зверев - Зверев Сергей Иванович (Вне закона, 2000)
Экземпляры: ф-21 (20221107) / Инвентарный номер: 58798 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6